PEMBERDAYAAN POKDARWIS SEBAGAI PENGGERAK DAN PENGEMBANGAN PARIWISATA DI DESA BULU CINDEA BUNGORO KABUPATEN PANGKAJENE DAN KEPULAUAN - Saleh, Firman; Kadir, Burhan; Latif, Aqilah Nurul Khaerani; Limola, Fajar Sidiq (Jurnal Ruhui Rahayu: Jurnal Pengabdian Masyarakat Ilmu Humaniora, 2024)
Tourism plays an important role in driving the village economy, with a focus on sustainability. One effective approach in tourism development is through the Tourism Awareness Movement. This concept involves various parties to create a favorable environment for tourism development, with an emphasis on education and awareness of the importance of preserving natural resources and local culture. The movement is realized through the formation of Tourism Awareness Groups (Pokdarwis), which play a role in managing tourism destinations at the village level by promoting cleanliness, safety, and environmental sustainability. Through collaboration between Pokdarwis, village governments, and local communities, village tourism can grow sustainably while providing economic and social benefits to the community. The Pangkep District Government develops tourism villages to improve economic growth, and community welfare, and preserve nature and local culture. Tourism villages not only provide tourist attractions but also integrate community life with local ordinances and traditions. Amidst challenges such as environmental management and infrastructure development, close collaboration between Pokdarwis, village governments, and local communities is key to success in optimally realizing the village's tourism potential. With the active participation of all relevant parties, village tourism can attract more tourist visits while preserving the culture and environment, by the principles of sustainable development that focus on the welfare of local communities.